2014
DOI: 10.1002/bit.25450
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid and glucose metabolism in fed‐batch CHO cell culture affects antibody production and glycosylation

Abstract: Fed-batch Chinese hamster ovary (CHO) cell culture is the most commonly used process for IgG production in the biopharmaceutical industry. Amino acid and glucose consumption, cell growth, metabolism, antibody titer and N-glycosylation patterns are always the major concerns during upstream process optimization, especially media optimization. Gaining knowledge on their interrelations could provide insight for obtaining higher immunoglobulin G (IgG) titer and better controlling glycosylation-related product quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
142
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(147 citation statements)
references
References 76 publications
5
142
0
Order By: Relevance
“…For example, in fedbatch culture of the human cell line rF2N78 producing a human IgG, Sin Seok Seo and colleagues (2014) observed that the increase of non-glycosylated antibody at the end of a culture without glucose feeding was not due to a deficiency in the expression of glycosylation enzymes but rather to insufficient precursor for glycosylation (Seo et al, 2014). Indeed, low glucose concentration leads to reduced intracellular concentration of UDP-GlcNAc and UDP-GalNAc (Fan et al, 2015;Villacrés et al, 2015). In our study, glucose depleted virtually at the same time of the culture and yet we observed a delayed production of IFNα2b of lower quality between the two types of cells thus suggesting an effect linked to the difference in the nutrient metabolism.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, in fedbatch culture of the human cell line rF2N78 producing a human IgG, Sin Seok Seo and colleagues (2014) observed that the increase of non-glycosylated antibody at the end of a culture without glucose feeding was not due to a deficiency in the expression of glycosylation enzymes but rather to insufficient precursor for glycosylation (Seo et al, 2014). Indeed, low glucose concentration leads to reduced intracellular concentration of UDP-GlcNAc and UDP-GalNAc (Fan et al, 2015;Villacrés et al, 2015). In our study, glucose depleted virtually at the same time of the culture and yet we observed a delayed production of IFNα2b of lower quality between the two types of cells thus suggesting an effect linked to the difference in the nutrient metabolism.…”
Section: Discussionmentioning
confidence: 96%
“…However, such approach can adversely impact protein quality, since it reduces the availability of nucleotide sugars, the key precursors for N-and O-glycosylations (Chee Furng Wong et al, 2005;Liu et al, 2014;Seo et al, 2014;Villacrés et al, 2015). On the other hand, the use of nutrient-rich media and concentrated feed solutions also present drawbacks as they may be associated with the generation of high amounts of metabolic by-products that can be detrimental to both productivity and protein quality (Andersen and Goochee, 1995;Fan et al, 2015). These observations highlight the important role of the central carbon metabolism on protein glycosylation.…”
Section: Introductionmentioning
confidence: 98%
“…Amino acids have been found to be associated with product quality, including glycosylation patterns (Aghamohseni et al 2014;Chen and Harcum 2005;Crowell et al 2007;Fan et al 2015), sequence variants (Yu et al 2009), aggregates, and fragments (Jing et al 2012;Yang and Butler 2000). However, the effect of amino acid on mAb charge variants has not been investigated.…”
Section: Introductionmentioning
confidence: 96%
“…Alternatively, high mannose/hybrids forms may be released early as a result of cell lysis. The detection of high mannose/hybrid glycoforms has been reported for other secreted recombinant proteins in mammalian cells 55, 56, 57, 58.…”
Section: Discussionmentioning
confidence: 89%